Use of National Consumer Survey Data to Explore Perceptions of Complementary and Alternative Medicine - Alina Cernasev; Basma Goma; Keri Hager; Lawrence Brown; Jon Schommer (INNOVATIONS in Pharmacy, 2020)
Background: Although Complementary and Alternative Medicine (CAM) has been the standard of therapy in Asia for centuries, it started receiving more attention in the U.S. in the last three decades.